Curative effect observation of full retinal laser photocoagulation and postoperative application of calcium dobesilate in the treatment of diabetic retinopathy - SHAOJinhua; CHENYaoruo (眼科学报; 卷 31, 编号 4 (December 2016): 《眼科学报》, 2016)
Objective: To investigate the curative effect of the postoperative retinal laser photocoagulation and calcium dobesilate in the treatment of diabetic retinopathy. Methods: Selected 96 patients, 175 eyes, randomly divided into control group (48 cases, 86 eyes) and study group (48 cases, 89 eyes). Two groups were all given retinal laser photocoagulation treatment, while the study group continued to receive calcium dobesilate for 12 weeks after treatment. After 12 weeks, observed the eyesight, change of blood rheology of the two groups. Results: After the treatment, the patients with vision >1.0 in the study group were significantly more than the control group(χ 2 =6.779, P=0.009), in the vision range of ≤0.4, 0.4~0.6, 0.7~1.0, the difference between the two groups was (χ 2 =0.003, P=0.955), (χ 2 =1.640, P=0.200), (χ 2 =2.148, P=0.143), respectively. After treatment, plasma viscosity, erythrocyte deposited, erythrocyte deformation index, fibrinogen in the study group were better than those in the control group (P 2 =6.302, P=0.012). Conclusion: The whole retinal laser photocoagulation and postoperative application of calcium dobesilate in treating the diabetic retinopathy can effectively improve eyesight and clinical curative effect, which may be associated with improving blood rheology.